Acceptance of Malaysia Sustainable Palm Oil (MSPO) among independent smallholders: case of Alor Gajah, Melaka / Muhammad Nur Qayyum Mohd Suhaimi and Firdaus Aziz - Mohd Suhaimi, Muhammad Nur Qayyum; Aziz, Firdaus (Faculty of Plantation and Agrotechnology, 2018)
In support of the development of sustainable palm oil and strengthening the image of the palm oil industry in Malaysia, YAB Prime Minister has announced the mandatory implementation of Malaysia's Sustainable Palm Oil Certification Scheme (MSPO) by 31 December 2019. MSPO will be implemented nationwide and will be the basis for palm oil branding Malaysia in the future. MSPO provides certification for private smallholders with seven (7) core principles, together with 22 criteria and 33 benchmarks. This study had been conducted to identify factors influence acceptance MSPO among independent smallholders. The input obtained by distributing random survey questions to 80 out of 100 respondents in the small districts of Alor Gajah, Melaka. Factors that can affect the acceptance in the implementation of MSPO are management commitment & responsibilities, transparency, compliance to legal requirement, and social responsibility, health, safety & employment conditions. The effect of each factor on the acceptance of MSPO can be identified by using Pearson and Double Linear Regression Correlation, and therefore the most important factor can be identified. Based on this project, management commitment & responsibilities is the factor that has the greatest impact on acceptance in the implementation of MSPO among independent smallholders. Through the use of Regression Analysis, the management commitment & responsibilities factor show the largest value of 0.436. Pearson's Correlation also showed a high value for the management commitment & responsibilities factor of 0.481 indicating that it has a very strong relationship with acceptance in implementing MSPO amongst independent smallholders.